Swimmers: Body fat mystery! - Burke, L. (Sportscience, 1997)
Two studies from Costill's Human Performance Laboratory at Ball State University have tried to address the energy balance oddity of swimmers. Jang et al.(1987) attempted to gain a crude measure of daily energy balance by comparing collegiate swimmers and collegiate distance runners. The other study by Flynn et al.(1990) examined energy and fuel usage during training sessions and recovery in swimming and running.